Characteristics of Thyroiditis Patients in Dr. Hasan Sadikin General Hospital in 2009–2013 - Sri Maryanti; Hasrayati Agustina; Mifatuhrachman Mifatuhrachman (Althea Medical Journal, 2016)
Background: It is reported that thyroid diseases affect around 200 milion people in the world. One of them is thyroiditis that may cause the risk of cancer. Moreover, thyroiditis can also cause hormonal disorders, such as hypothyroid and hyperthyroid. It is assumed that thyroiditis has distinctive clinical characteristics. The aim of this study was to evaluate the characteristics of thyroiditis based on age, gender, location, and clinical features of the patient.Methods: The study was conducted using descriptive-retrospective method. The data were collected from patients’ medical records through total sampling from January 2009 to Desember 2013 in Dr. Hasan Sadikin General Hospital, Bandung.Results: It was found 35 cases of thyroiditis. Based on the histopathological type, the most frequently found thyroiditis was Hashimoto’s thyroiditis. Based on age, thyroiditis mostly affected people at age 41–60 years old. Based on the gender, thyroiditis mostly affected female and the location of lesions were bilateral. The majority clinical features of patients were hypothyroid in Hashimoto’s thyroiditis, hyperthyroid in acute thyroiditis, and normothyroid in sub-acute granulomatous thyroiditis.Conclusions: Based on age, gender, and the location, the majority type of thyroiditis did not show specific characteristics. However, thyroiditis showed specific characteristics based on the clinical features of patient. [AMJ.2016;3(1):49–53]DOI: 10.15850/amj.v3n1.701